Ageing meets kidney disease. (30th June 2022) - Ortiz, Alberto; Mattace-Raso, Francesco; Soler, María José; Fouque, Denis
Abstract: Chronic kidney disease (CKD) is defined as abnormalities of kidney structure or function, present for >3 months, with implications for health. The most used diagnostic criteria are a urinary albumin: creatinine ratio ≥30 mg/g or an estimated glomerular filtration rate (eGFR) <60 mL/min/1.73 m 2 . Either of these diagnostic thresholds is associated with adverse health outcomes. GFR decreases with age and the prevalence of CKD is highest in older adults; moreover, the presence of CKD is associated with an increased risk of all-cause and cardiovascular death related to accelerated ageing in all age ranges, and the absolute increase in risk is highest for those aged >75 years. Indeed, premature death is a more common outcome than CKD progression to kidney failure requiring kidney replacement therapy. The progressive ageing of the world population contributes to the projection that CKD will become the second most common cause of death before the end of the century in countries with long life expectancy. The current collection of selected studies on kidney disease and ageing published in Age&Ageing, NDT and CKJ provides an overview of key topics, including cognitive decline, sarcopaenia, wasting and cardiovascular and non-cardiovascular morbidity and mortality, the management of kidney failure and gender differences in CKD progression.